Using deliberative democracy to identify energy policy priorities in the United States. (July 2015) - Canfield, Casey; Klima, Kelly; Dawson, Tim
Abstract: Energy policies to mitigate and adapt to climate change need public support to be successful. Deliberative democracy forums serve to both better inform the public of the available options and provide a way for policymakers to assess support for proposed policies. This work uses a pilot study in Pittsburgh to generate hypotheses regarding how a deliberative democracy process affects residents' perceptions of and support for City-wide energy policies to address climate change. A convenience sample completed pre and post-surveys during a deliberative forum: "Building a Resilient Pittsburgh: Climate Challenges and Opportunities". The surveys focused on knowledge, perceptions, and opinions related to the existence of climate change as well as energy policies to mitigate and adapt to climate change. Results suggest that the forum was useful in shifting perceptions, but did not significantly influence objective knowledge or policy support. Participants had a slight preference for energy efficiency strategies over renewable energy and public information. More research is needed to evaluate deliberative democracy approaches and expand these findings to a more diverse population.